RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica Juncea L.) AKIBAT PEMBERIAN PUPUK KANDANG SAPI DAN BIOURINE SAPI - I Gusti Ayu Diah Yuniti; I Putu Sujana; I Made Sukerta; Komang Dean Ananda; Oktaviani Nawul (Agrofarm: Jurnal Agroteknologi, 2024)
Brassica juncea L. or commonly called mustard greens is one of the most popular types of vegetables in Indonesia, because this mustard is one of the varieties that contain various health benefits. This study aims to determine "Response of Growth and Yield of Green Mustard (Brassica Juncea L.) due to the application of cow manure and cow biourine". The method used is a Randomized Block Design (RBD) with factorial treatment with 2 treatment factors. Factor 1: Dosage of cow manure with 5 levels, namely K0 (without cow manure), K1 (cow manure 30 g / 10 kg of soil), K2 (cow manure 60g / 10 kg of soil), K3 (cow manure) 90 g / 10 kg of soil), and K4 (cattle manure 120 g / 10 kg of soil). Factor 2: the concentration of cow biourine with 5 levels, namely B0 (without cow biorine), B1 (cow biorine 80 ml / 1 liter of water), B2 (bovine biorine 160 ml / 1 liter of water), B3 (cow biorine 240 ml / 1 liter water), and B4 (beef biorine 320 ml/1 liter of water). The results showed that the treatment with doses of 120 g / 10 kg of soil (K4) gave the best growth compared to other treatment with doses of manure for all observation parameters such as plant height (cm), number of leaves (strands), leaf area. (cm²), total plant fresh weight (g), total plant oven dry weight (g), fresh weight without plant roots (g), and oven dry weight without plant roots (g). as well as the treatment with 320 ml / 1 liter of water (B4) concentration of cow biourine